2019
DOI: 10.1177/0269881119858306
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cannabidiol (CBD) on low-frequency activity and functional connectivity in the brain of adults with and without autism spectrum disorder (ASD)

Abstract: Background: The potential benefits of cannabis and its major non-intoxicating component cannabidiol (CBD) are attracting attention, including as a potential treatment in neurodevelopmental disorders such as autism spectrum disorder (ASD). However, the neural action of CBD, and its relevance to ASD, remains unclear. We and others have previously shown that response to drug challenge can be measured using functional magnetic resonance imaging (fMRI), but that pharmacological responsivity is atypical in ASD. Aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 50 publications
1
65
0
5
Order By: Relevance
“…179 Patients with autism spectrum disorder were administered 600 mg of CBD and they also showed changes in functional connectivity as assessed by the fractional amplitude of low-frequency fluctuations. 180 While the direct underlying mechanism by which CBD regulates functional connectivity requires more research, there is a clear therapeutic effect on functional connectivity following CBD intake.…”
Section: Cerebrovasculaturementioning
confidence: 99%
“…179 Patients with autism spectrum disorder were administered 600 mg of CBD and they also showed changes in functional connectivity as assessed by the fractional amplitude of low-frequency fluctuations. 180 While the direct underlying mechanism by which CBD regulates functional connectivity requires more research, there is a clear therapeutic effect on functional connectivity following CBD intake.…”
Section: Cerebrovasculaturementioning
confidence: 99%
“…Participants were mainly children, even if in two studies there were mixed samples [53,54]. The three studies conducted by Pretzsch and colleagues [55][56][57] included only adults with normal cognitive abilities (IQ>70). Interestingly, only another study [58] has specified the level of functioning, which was not reported in the remaining papers.…”
Section: Characteristics Of Studies and Participantsmentioning
confidence: 99%
“…McVige et al [60] documented the use of medical cannabis with unspecified composition. Finally, Pretzsch and colleagues administered single doses of 600 mg of CBD or CBDV [55][56][57]. Only the studies by Pretzsch et al used a control treatment (placebo).…”
Section: Characteristics Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10][11] The remaining nine articles consisted of a viewpoint, ethics statement, letter, two studies done on adult populations, and four studies done using cannabis-based products for the treatment of autism related symptoms in children. [12][13][14][15][16][17][18][19][20] The 2019 Schleider et al article was about a prospective study looking at the safety and efficacy of medical cannabis treatment in children with ASD. 17 A CBD:THC solution of 30% to 1.5% was used in 188 children with ASD who had comorbid behavioral symptoms.…”
Section: Related Literaturementioning
confidence: 99%